The Future of HR Ecosystem for Business Sustainability of Indian MSMEs: Assessing the Trends, Opportunities and Challenges - Juster, Charles (Digital Repository of Theses, 2026)
This is an exploratory study on the evolving role of Human Resources (HR) ecosystem within Indian Micro, Small, and Medium Enterprises (MSMEs) which is considered as the backbone of Indian economic growth. Despite their significant contribution to the Indian economy, MSMEs face unique challenges that often impede their development and competitive stance. This study delves into these challenges, particularly focusing on the Human Resource Management (HRM) which is a neglected area, to unveil the opportunities and strategies essential for fostering a robust, efficient and business driven HR ecosystem that contributes to business sustainability of Indian MSMEs. The research objectives encompass a comprehensive identification and analysis of the HR ecosystem and challenges in Indian MSMEs, assessing the impact of elements of HR ecosystem on business growth and sustainability, exploring opportunities within the HR ecosystem, and developing strategic recommendations to build competitive advantage through people practices in these enterprises. Understanding the HR ecosystem’s influence on business sustainability involves a deep dive into how these ecosystem elements and sustainability parameters are interlinked. The study also explores the impact of different elements of HR ecosystem on the business sustainability parameters. The methodology proposed is a mixed-method approach, integrating both qualitative and quantitative data collected through literature reviews, surveys, and interviews with stakeholders in the MSME sector. Quantitative data were analysed with AMOS for understanding the dynamics between the variables and for testing of the study hypotheses. The qualitative data were analysed through manual thematic analysis technique. The adoption of an ecosystem approach in HR management could emerge as a potential game-changer for building business resilience and sustainability for Indian MSMEs. The insights form this exploration would be helpful to the owners, managers, practitioners, consultants, HR service providers and government agencies to look into the current status of the HRM practices in MSMEs and redesign them from a business-driven ecosystem perspective for thriving their business in a challenging business environment rather than relying on silo practices and the practices followed by larger organizations which have a different business context. Key Words: MSMEs, Geen HRM, Business Sustainability, HR ecosystem, People Capability Maturity Model, Gig economy, Formalization of HR, Ethical Governance, Employee Experience, Legal compliance behaviour, Digital HR, Environmental & Social responsibility, Technology adoption capability, Positive work culture, Strategic HR framework, Economic viability, Customer & Stakeholder loyalty, Employer Image, Organisational Agility & Responsiveness, Innovation, Employee Engagement, Employee retention.